2012
DOI: 10.1007/s11748-012-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

Is the mid-term outcome of free right internal thoracic artery with a proximal anastomosis modification inferior to in situ right internal thoracic artery?

Abstract: By modifying the proximal anastomosis of the free RITA, cardiac events may be decreased, while survival and graft patency comparable with in situ RITA can be obtained, and a significantly larger number of targets can be revascularized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Several configurations have been used to accomplish TAR of left-sided coronary system with bilateral internal mammary arteries (BIMA) only [13] . These include in situ right internal mammary artery (RIMA) to the left anterior descending (LAD) artery and the left internal mammary artery (LIMA) to circumflex marginal branches [14] [ Figure 1], routing the RIMA through the transverse sinus in a retroaortic course [15] [ Figure 2], and free RIMA grafts anastomosed proximally either to the LIMA [16] [ Figure 3] or to the ascending aorta [17] . Table 1 summarizes the pros and cons of these configurations.…”
Section: Bilateral Internal Mammary Arteriesmentioning
confidence: 99%
“…Several configurations have been used to accomplish TAR of left-sided coronary system with bilateral internal mammary arteries (BIMA) only [13] . These include in situ right internal mammary artery (RIMA) to the left anterior descending (LAD) artery and the left internal mammary artery (LIMA) to circumflex marginal branches [14] [ Figure 1], routing the RIMA through the transverse sinus in a retroaortic course [15] [ Figure 2], and free RIMA grafts anastomosed proximally either to the LIMA [16] [ Figure 3] or to the ascending aorta [17] . Table 1 summarizes the pros and cons of these configurations.…”
Section: Bilateral Internal Mammary Arteriesmentioning
confidence: 99%
“…Thus, the graft flow might not be affected each other, and this proximal anastomosis seemed to minimize the flow competition or steal phenomenon. A previous report about this type of anastomosis showed that the patency of one graft was not affected by the patency of the other graft 12) . Furthermore, the stenosis grade of the target vessel reportedly does not affect the patency rate of the RITA at follow-up angiography 6) .…”
Section: Discussionmentioning
confidence: 81%
“…Buxton and colleagues 17) reported that the highest RITA failure rates were associated with grafting a native coronary artery with < 60% stenosis compared with 80-100%, and with grafting the right coronary artery. In another study, good mid-term free RITA patency rates were reported using only the left circumfl ex artery with a high degree of stenosis (mean 87.1 %) 12) . In our present study, the mean fl ow in the free RITA used as an individual grafting to the target coronary artery with mild proximal stenosis was low.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations